Preliminary investigation and application of population genetics asymmetric island model in the attribution of sporadic cases of Campylobacter infection in China - ZHANG Liyun; YE Xin; LIU Zhaoping; WANG Yibaina (Zhongguo shipin weisheng zazhi, 2024)
ObjectiveThe application of population genetics model was explored to determine the main sources leading to sporadic cases of human Campylobacter infection.MethodsMLST data from PubMLST public database was analyzed to assign Campylobacter sporadic cases to various sources by using the population genetics asymmetric island model （AIM）.ResultsAs a result of sporadic cases of Campylobacter infection， chickens （50.49%） accounted for the highest percentage， followed by ducks and geese， cattle， pigs （22.56%， 18.36% and 4.52%， respectively）， whereas the environment and wild birds accounted for a lower percentage （0.78% and 0.66%， respectively）.ConclusionBased on microbial molecular typing data and statistical modeling， this study quantitatively assessed the contribution of different sources to sporadic cases of Campylobacter infections in China， using the AIM for source attribution practice. It provided directions and ideas for the next stage of source attribution for foodborne diseases.